2021
DOI: 10.3389/fphar.2021.746725
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy of Novel Photosensitizer Ameliorates TNBS-Induced Ulcerative Colitis via Inhibition of AOC1

Abstract: Ulcerative colitis (UC), a chronic, nonspecific inflammatory bowel disease characterized by continuous and diffuse inflammatory changes in the colonic mucosa, requires novel treatment method. Photodynamic therapy (PDT), as a promising physico-chemical treatment method, were used to treat UC rats’ model with novel photosensitizer LD4 in this paper, the treatment effect and mechanism was investigated. LD4-PDT could improve the survival rate of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced UC model rats, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Moreover, a recent study reported that LD4-PDT facilitated the healing of colonic mucosa, regulated gut microbiota, and ameliorated clinical symptoms of UC 19 . This study presents compelling evidence supporting the multifaceted effects of LD4-PDT, which include the regulation of inflammatory cytokine balance and modulation of gut microbiota composition.…”
Section: The Mechanisms Of Pdt In Intestinal-related Inflammatory And...mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, a recent study reported that LD4-PDT facilitated the healing of colonic mucosa, regulated gut microbiota, and ameliorated clinical symptoms of UC 19 . This study presents compelling evidence supporting the multifaceted effects of LD4-PDT, which include the regulation of inflammatory cytokine balance and modulation of gut microbiota composition.…”
Section: The Mechanisms Of Pdt In Intestinal-related Inflammatory And...mentioning
confidence: 98%
“…PDT offers several advantages, including minimally invasive procedures, dual-targeted killing, minimal toxicity and side effects, and the potential for repeated treatments 1 . It fulfills the criteria for the aforementioned new treatment options for IBD 19 . Numerous studies have showcased the considerable advantages of PDT in treating inflammatory diseases, including IBD 4 , 36 , 37 .…”
Section: Advantages Of Pdt In Intestinal-related Inflammatory and Can...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, several PSs, such as 5-aminolevulinic acid (5-ALA) and temoporfin, have been approved for cancer therapy ( Fotinos et al, 2006 ). Notably, with the development of endoscopy and fiberoptic technologies, PSs (e.g., 5-ALA) have been applied to treat gastrointestinal diseases, such as ulcerative colitis ( Rong et al, 2021 ). In fact, Reinhard et al (2015) reported a liposomal formulation of meta-tetra (hydroxyphenyl) chlorin that alleviated colitis and prevented colitis-associated carcinogenesis in mice.…”
Section: Photosensitizers and Nanoparticular Delivery Systemsmentioning
confidence: 99%
“…Photodynamic therapy (PDT), a non-invasive therapeutic approach employing light irradiation and photosensitizers (PSs) to remove unwanted cells, has been proven efficacious for the treatment of several diseases, including cancers ( Zheng et al, 2020 ; Zou et al, 2021 ), cardiovascular disease ( Kim et al, 2013 ), inflammatory bowel disease ( Rong et al, 2021 ), and diabetic ocular disease ( van Rijssen et al, 2021 ). Compared with traditional treatment methods such as surgery, radiotherapy, and chemotherapy, PDT exhibited efficient therapeutic action and low systemic toxicity ( Feng et al, 2020 ; Gunaydin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%